Dealing with the prejudices towards Islam - Abd Razak, Dzulkifli (2008)
forum held at about the same time is fast falling into oblivion. Many seem to be more preoccupied with the former rather than spending their energy building on the successes accrued from the latter. The twoday forum, organised by the National Unity and Integration Department, came up with 10 recommendations ("Positive start to religious dialogue"—New Sunday Times, Aug 10). Although the spokesman of the forum admitted that the participants were burdened by stereotyped images of each other, many points were in fact raised, explained and clarified on a hearttoheart basis. "They proved themselves wrong and they showed that they were mature and strong enough to listen."